2018
DOI: 10.7324/japs.2018.8702
|View full text |Cite
|
Sign up to set email alerts
|

Mango mistletoe Dendrophthoe pentandra leaf extract acts synergistically with 5-Fluorouracil to induce apoptosis and increase p21 expression in human cervical adenocarcinoma HeLa cells by reducing survivin expression

Abstract: Mango mistletoe (Dendrophthoe pentandra L. Miq) (MMDP) leaf extract which contained quercetin inhibits cancer cells. MMDP increasing effectively of 5-Fluorouracil (5-FU) as a chemotherapy agent. This study aimed to investigate the synergistic effects of MMDP combined with 5-FU to determine the percentage of apoptosis, p21, and survivin in HeLa cells. Flow cytometry analysis revealed that it increases apoptosis HeLa cell through increasing p21 and also decreased survivin percentage. The combination of 5-FU 5 µg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Dendrophthoe pentandra, a mango-growing parasitic plant, has commonly been used as a medicinal plant for treating asthma, measles, cough, skin infections and has been used as a diuretic and an anticancer agent (Artanti et al, 2012). Dendrophthoe pentandra contains both of kaempferol-3-0-alpha-L-rhamnopyranoside and quercetin-3-0-alpha-L-rhamnopyranoside to prevent colon cancer proliferation (Wiart, 2012;Endharti et al, 2018a). The combination with doxorubicin decreased survivin and iCa 2+ concentrations (Endharti et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dendrophthoe pentandra, a mango-growing parasitic plant, has commonly been used as a medicinal plant for treating asthma, measles, cough, skin infections and has been used as a diuretic and an anticancer agent (Artanti et al, 2012). Dendrophthoe pentandra contains both of kaempferol-3-0-alpha-L-rhamnopyranoside and quercetin-3-0-alpha-L-rhamnopyranoside to prevent colon cancer proliferation (Wiart, 2012;Endharti et al, 2018a). The combination with doxorubicin decreased survivin and iCa 2+ concentrations (Endharti et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the ethanolic extract of DP combined with doxorubicin could decrease intracellular calcium concentration and surviving levels and increase the number of apoptotic MCF-7 cells, which exhibited more significant cytotoxic effects than doxorubicin alone ( Endharti et al, 2018b ). Compared with the 5-fluorouracil only group, the combination of ethanolic extract of DP and 5-fluorouracil more significantly decreased the survival of HeLa cells by increasing the percentage of p21 and apoptosis, showing a synergistic effect to restrain the proliferation of tumor cells ( Endharti et al, 2018a ). The ethanolic extract nanoparticles of DP together with cisplatin could produce a synergistic effect on HeLa cells, which possessed more significant cytotoxic effects than individual medicines ( Mutiah et al, 2018 ).…”
Section: Applicationsmentioning
confidence: 99%
“…According to Artanti et al [4] D. pentandra contains a major group of flavonoids that contribute to its antioxidant activ ity. However, several studies also reported the pharmacological effect of flavonoids from D. pentandra, such as antioxidants [7], antibacterial [7], anticancer [12,18], and anti-inflam…”
Section: Flavonoidsmentioning
confidence: 99%
“…According to Artanti et al [4], D. pentandra contains a major group of flavonoids that contribute to its antioxidant activity. However, several studies also reported the pharmacological effect of flavonoids from D. pentandra, such as antioxidants [7], antibacterial [7], anticancer [12,18], and anti-inflammatory [20] activities. Currently, only certain flavonoids have been detected in this plant, such as quercitrin, quercetin, and flavonol glycoside [4,62] (Figure 6).…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation